2004
DOI: 10.1152/ajplung.00388.2003
|View full text |Cite
|
Sign up to set email alerts
|

Substance P and neutral endopeptidase in development of acute respiratory distress syndrome following fire smoke inhalation

Abstract: To characterize the tachykininergic effects in fire smoke (FS)-induced acute respiratory distress syndrome (ARDS), we designed a series of studies in rats. Initially, 20 min of FS inhalation induced a significant increase of substance P (SP) in bronchoalveolar lavage fluid (BALF) at 1 h and persisted for 24 h after insult. Conversely, FS disrupted 51.4, 55.6, 46.3, and 43.0% enzymatic activity of neutral endopeptidase (NEP, a primary hydrolyzing enzyme for SP) 1, 6, 12, and 24 h after insult, respectively. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…This was manifested by thickening of the alveolar capillary membrane, interstitial pneumonitis, peribronchiolar inflammation, and sloughing and necrosis of the bronchiolar epithelium. These observations are consistent with previously published findings (1,22).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was manifested by thickening of the alveolar capillary membrane, interstitial pneumonitis, peribronchiolar inflammation, and sloughing and necrosis of the bronchiolar epithelium. These observations are consistent with previously published findings (1,22).…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have demonstrated that SP is a proinflammatory agent that influences various signaling transduction pathways within a complex inflammatory network by C-fiber afferent stimulation following external stimulation (1,4,9,14,22). In vivo studies have demonstrated the efficacy of antioxidants and free radical scavengers in ameliorating increases in endogenous SP levels (which may result in increased microvascular permeability via upregulated ICAM-1 expression, edema, and severe hypoxia) (11).…”
Section: Discussionmentioning
confidence: 99%
“…This ligand-receptor pair mediates neurogenic inflammation in the airways via cytokines including IL-1, IL-6, and TNF-␣ (14,20). In addition, substance P levels are markedly elevated in pulmonary edema fluid from ARDS patients (6), and the NK-1 receptor has been implicated in the pathophysiology of lung injury associated with pancreatitis (13), smoke inhalation (30), and viral infections (23) including respiratory syncytial virus (11).…”
mentioning
confidence: 99%
“…The NK1 receptors involved in plasma leakage are located on the endothelial cells of post capillary venules and collecting venules. Within seconds of the activation of NK1 receptors by substance P, gaps form in the endothelium of target vessels (Wong et al 2003 and 2004). The endothelial gaps are transient, and the leak normally ends in a few minutes (McDonald et al 1996).…”
Section: Discussionmentioning
confidence: 99%